Reading Proficiency Level of Grade 1 Pupils Using Text-to-Speech - Imus, Jasmin Krissa R; Resultay, Razeale G (ASEAN Multidisciplinary Research Journal, 2019)
The study was conducted to determine the reading proficiency level of the Grade 1 Learners during the S.Y. 2019 - 2020. The quasi-experimental design was used and the questionnaire was the main data gathering instrument. The data were statistically analyzed using frequency, percentage, and serial correlations in the treatment of data. The study reveals that the number of male and female was almost the same. Most of them have an average grade within very satisfactory in the MTB-MLE subject. They speak Pangasinan at home and use coloring books as their reading material. Their parents are mostly college graduate and with a modest family income. It shows that majority has cellphone available at home as their media-gadget. The study further reveals that the learners’ reading proficiency levels after exposure to text-to-speech show improvement to their word recognition and comprehension that step –up to instructional and independent level. Thus, the level of reading proficiency after exposure to their respective teaching strategy is statistically significant as such that there is an effect in teaching the learners using text-to-speech than those taught in conventional way. This study recommended that considering the contemporary world that we are now living in, technology should be made available on an equitable basis like the use of text-to-speech in improving pupils’ learning and reading development. Teachers need to adopt new strategies like text-to-speech for teaching reading comprehension in order to support struggling learners to improve their achievement since it is a significant indicator of learners’ academic success. Also, provide opportunities to reading teachers for professional development by sending them in trainings, seminars, workshops and symposia especially designed to enhance teacher’s skills in teaching reading using technology and uplifting the reading proficiency of the pupils.